Remarkable lives: Robert Lawrence in conversation with Jerome Carson. Issue 2 (6th December 2019) - Lawrence, Robert; Carson, Jerome
Abstract : Purpose: The purpose of the paper is to provide a profile of Robert Lawrence. Design/methodology/approach: Robert provides a short background to his life and is then interviewed by Jerome. Findings: Robert talks about the slow onset of his condition, his hospital admission and subsequent long journey of recovery. Research limitations/implications: Case studies are of course only one person's story. The world of someone experiencing psychosis is so different that we can only really understand it fully through the accounts of sufferers like Robert. Practical implications: Robert makes a number of points about how services could be improved, such as through quicker and better treatment and a commitment to promote positive mental health. Social implications: Robert talks about "benefits you can live off." He notes that some governments have not fully appreciated the reality of mental suffering and its effects on trying to live a "normal" life. Originality/value: Robert's story has seen him embark on a long journey. He has now managed to study for a qualification which will hopefully bring him employment as a counsellor.